A Clinical Study to Evaluate the Comparative Efficacy of Phaltrikadi Kashaya and Phaltrikadi Kashaya Ghana Vati in the Management of Non-Alcoholic Fatty Liver Disease (AYUSHDHARA, 2025)
The non-alcoholic fatty liver disease (NAFLD) has emerged as a leading type of chronic liver disease and a hepatic manifestation of “metabolic syndrome” worldwide. The emerging epidemic of childhood obesity means that increasing numbers of young people have NAFLD and early diagnoses followed by management are important. The only treatment options in early stages are weight loss, dietary fat reservation and exercise with strict control of associated diseases. A formulation mentioned in Ayurveda is Phaltrikadi Kashaya which is a combination of 8 widely used hepatoprotective herbs. But, since its preparation as a Kwatha in itself is a cumbersome task, so the present study has been planned to assess the comparative efficacy of Phaltrikadi Kashaya and Phaltrikadi Kashaya Ghana Vati in the management of NAFLD. 50 patients, within the age of 18-70 years, having aspartate amino-transferase (AST/SGOT) and alanine transaminase (ALT/SGPT) levels twice the upper normal limit and ultrasonographical evidence of fatty infiltration of liver, were selected and divided into 2 groups consisting of 25 patients each. Group I was managed with Phaltrikadi Kashaya in the dose of 50ml twice a day whereas, Group II was managed with Phaltrikadi Kashaya Ghana Vati in the dose of 500mg tablet, twice a day for a period of 12 weeks. Both subjective and objective parameters were assessed before and after the completion of trial. Data obtained during the trial was then tabulated and statistically analysed.